KREDIBILITAS SITUS SAHAM ONLINE: PENDEKATAN USABILITAS, DESAIN DAN INFORMASI KONTEN SITUS BURSA EFEK INDONESIA - Effy Z Rusfian; Irwansyah Irwansyah; Niken F Ernungtyas (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2017)
Credibility of website especially on trading market is important for shareholders to get stockexchange information. Websites are the extension of organization that could attract business’s target market and potential customer. However, previous studies found that usability, design, and content may affect the website credibility.  Many stock exchange markets such as Nigerian/NSE, Baku/BSE, Irish/ISE, Mauritus/SEM including Securities and Exchange Commission/SEC concerned and improve about their website. This study aims to observe variable of usability, design and content which affect website credibility on Indonesia context especially with idx.co.id as a treatment. This reaserch method using quasi-experiment with 30 participants with the equivalent time-samples design and adopting Bipolar Emotional Response Testing (BERT), this study found that website credibility was explained about 51.6% by usability, design, and information variables. Moreover, information variable contributed bigger than other two variables while usability variable did not contribute significantly. Specifically, information variable become important for the credibility of website which did not have transaction feature.